Nitrogen Mineralization of Apple Orchard Soils in Regions of Western and South-Eastern Norway - Tore Krogstad; Valentina Zivanovic; Aleksandar Simic; Milica Fotiric Aksic; Vlado Licina; Mekjell Meland (Agronomy, 2023)
The mineralization of nitrogen in apple orchard soil will increase the soil supply. An incubation study to test the soil potential and the validity of analytical methods was conducted at 3, 8, 15, and 20 °C for up to 128 days on soils from western and south-eastern Norway. Soils with the highest pH showed the highest mineralization. The mineralization increased with increasing temperature and time, but start-up N reduced mineralization. The mineralization cannot be estimated from standard soil chemical parameters because the different C/N ratio indicates organic material of different origin and quality. The increase in NO3-N started very quickly and ranged from 17 to 182% and 12 to 64% after 8 days at 3 °C and 20 °C, respectively. There was no correlation between total N in the soil and the amount of mineralized N. On average, the mineralization increased by 5–7% for a change of 1 °C in the interval from 8 to 15 °C in the soil. The chemical extraction method using heated KCl correlated well with the mineralization data. On average, the chemical method estimated 30 kg N ha−1, which corresponded to 0.48% of total N. Recommendations for N fertilization based on total N in the soil overestimate the contribution of plant-available N in most cases.